Coordinating Higher Education as an e-Government Initiative - Cherednichenko, Olga; Kuklenko, Dmytro; Zlatkin, Sergiy (My University, 2006)
Government plays a key role in providing higher education. It supplies policies and regulations, information to the society, administers funds and licensing, develops standards, etc. In the context of total e-Governing Ministries of Education of many countries initiated the creation of supporting information systems. These systems in most cases are limited to providing information resources of different kinds to the society by web-portals. Administering and coordinating functions are left out for some reasons. In this paper we discover the typical structure of higher education, different stakeholders involved in the process of providing higher education services, information and data flows. We discuss the key functions that information systems must support. And finally we propose the e-Government higher education reference model to be addressed when developing such information systems.